2013
DOI: 10.1007/s10950-013-9386-z
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of ground motion relations for seismic hazard analysis

Abstract: We introduce a new approach for ground motion relations (GMR) in the probabilistic seismic hazard analysis (PSHA), being influenced by the extreme value theory of mathematical statistics. Therein, we understand a GMR as a random function. We derive mathematically the principle of area-equivalence; wherein two alternative GMRs have an equivalent influence on the hazard if these GMRs have equivalent area functions. This includes local biases. An interpretation of the difference between these GMRs (an actual and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The results demonstrated that a superior fit to the data and, in turn, more accurate acceleration estimates are obtained under the latter assumption. Similar considerations were expressed by Raschke (2013), who criticized the log-normal assumption and noted that the GEVD is the natural distribution for residuals of maxima such as PGA. Huyse et al (2010) applied the peaks over threshold method to analyse both the raw PGA data and the logarithmic residuals of PGA, and concluded that the generalised Pareto distribution (GPD), with the negative shape parameter, provided a model that was more accurate for the tail fractions of both the studied datasets.…”
Section: Introductionmentioning
confidence: 57%
“…The results demonstrated that a superior fit to the data and, in turn, more accurate acceleration estimates are obtained under the latter assumption. Similar considerations were expressed by Raschke (2013), who criticized the log-normal assumption and noted that the GEVD is the natural distribution for residuals of maxima such as PGA. Huyse et al (2010) applied the peaks over threshold method to analyse both the raw PGA data and the logarithmic residuals of PGA, and concluded that the generalised Pareto distribution (GPD), with the negative shape parameter, provided a model that was more accurate for the tail fractions of both the studied datasets.…”
Section: Introductionmentioning
confidence: 57%
“…The latter is a result of extreme value statistics (cf. Schlather, 2002, theorems 1 and 2), as was mentioned already for PSHA by Raschke (2013a).…”
Section: Influence On the Pshamentioning
confidence: 62%
“…However, this leads to an overestimation of the dispersion measures V(ε a ) and σ a =√V(ln(ε a )) and, consequently, results in a global overestimation of the seismic hazard (cf. Raschke, 2013a). I particularly emphasise that a global overestimation of V(ε a ) and σ a cannot compensate for the local biases of Fig.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations